Nature abhors a circle. (12th December 2018) - Loutrel, Nicholas; Liebersbach, Samuel; Yunes, Nicolás; Cornish, Neil
Abstract: The loss of orbital energy and angular momentum to gravitational waves produced in a binary inspiral forces the orbital eccentricity to adiabatically evolve and oscillate. For comparable-mass binaries, the osculating eccentricity is thought to decrease monotonically in the inspiral. Contrary to this, we here show that, once the osculating eccentricity is small enough, radiation reaction forces it to grow secularly before the binary reaches the last stable orbit. We explore this behavior, its physical interpretation and consequences, and its potential impact on future gravitational wave observations.